Тheoretical aspects of evaluating the efficiency of managerial activities of the heads of general secondary education institutions - Vorobiova, N. (Problems of Engineer-Pedagogical Education, 2019)
Granting general secondary education institutions, viewed as subjects of educational activity, the right to self-government, which means their autonomy, independence and responsibility to make decisions regarding academic (educational), organizational, financial, personnel-related and other issues, as well as changes at the legislative level concerning the procedure for appointing school heads, necessitates the search for new managerial models and approaches to assessing professional activity of managers of education Existing approaches to assessing the effectiveness of managerial activity of school principals do not allow checking their professional competence completely. Clear criteria, adapted to the current trends in education, are expected to help in the formation of an objective assessment of the activities of heads of general secondary education institutions, promote the improvement of both the system of managing general secondary education in general and the development of managerial competence of school principals, encourage them to grow professionally, creating a positive image of their institutions of general secondary education, which, in turn, ensures the quality of educational services.